Rel governs loser elimination during stem cell competition in the Drosophila testis. - Hof-Michel, S.; Cigoja, L.; Huhn, S.; Bökel, C. (European Journal of Cell Biology, 2024)
In the Drosophila testis, a group of stromal cells termed hub provides multiple niche signals for the surrounding germline and somatic stem cells. Stem cells of both populations compete for physical retention in the niche, and clones unable to transduce any one niche signal are rapidly eliminated from the stem cell pool by differentiation. We have mapped the transcriptomes of isolated somatic cyst stem cells and differentiated cyst cells, and found that the stem cells but not their differentiated progeny exhibit the signature of an innate immune response including the NF-?B transcription factor Relish (Rel). Related signalling pathways had previously implicated in cell competition in larval epithelia, prompting the question of whether NF-?B signalling was, despite the clear differences between the two competition scenarios, also involved in stem cell competition in the testis. Here we show i) that in the testis Rel is dispensable for stemness, ii) that loss of Rel or the upstream receptor Toll suppresses loser elimination following a variety of different triggers used to induce loser fate, and iii) that clonal Rel activation is sufficient for the displacement of neutral or winner cells from the niche, even if these cells otherwise retain stem cell properties.